UMP’s excellent Graduate Employability up a notch to 96% - UMP, PNC (2019)
Universiti Malaysia Pahang’s (UMP) annual ranking of Graduate Employability (GE) remains excellent, and in fact, rose one percent to 96 percent, compared to the 95 percent it recorded last year.